Dimensions of Citizenship and Nationality in the Area of Comprehensive Education: Experience of the Republic of Lithuania - Grincevičienė, Vilija; Klimka, Libertas (Zakład Edukacji Międzykulturowej i Badań nad Wsparciem Społecznym Wydziału Nauk Historycznych i Pedagogicznych Uniwersytetu Wrocławskiego, 2017)
This paper is a discourse on what could be the present strategy of reinforcing the fundaments of the state. Has nationality, which is being instilled in public education as ethnic culture, lost its meaning for that purpose? The conclusions state that the reinforcement of ethnic culture is a goal of national importance and it has to be efficiently implemented in the institutions of education and culture. This is also important in the schools of national minorities in pursuance of closer cooperation and integrity of the society. The paper also contains insights about a slightly different view on integration in region’s cultural space, held by ethnic minorities in Lithuania.
Keywords: citizenship; comprehensive education; ethnic culture; cultural heritage; identity; nationality